Case report: Ultrasound-guided needle knife technique for carpal ligament release in carpal tunnel syndrome treatment - Sun, Jianjun; Zou, Xiaodi; Fu, Qinyun; Wu, Jianhua; Yuan, Shuaishuai; Alhaskawi, Ahmad; Dong, Yanzhao; Zhou, Haiying; Abdalbary, Sahar Ahmed; Lu, Hui (Frontiers in Neurology, 2023)
Carpal tunnel syndrome (CTS) is a common peripheral neuropathy of the hand, mainly manifesting as sensory disturbances, motor dysfunctions, and pain in the fingers and hand. The pathogenesis of the disease is associated with fibrosis of the transverse carpal ligament in the carpal tunnel, which compresses median nerve. In our case, we demonstrate an ultrasound-guided needle knife technique to treat CTS. We guided the patient to a supine position on the examination table. The skin of the wrist area was sterilized for the procedure. After the skin was dry, we positioned sterile drapes, located the median nerve and compression, and marked the compression point. Local anesthesia was administered. An ultrasound-guided needle knife was inserted. The needle knife was advanced under ultrasound guidance. The carpal ligament was incised. A gradual release of pressure on the median nerve was observed on the ultrasound monitor. After treatment, the patient’s finger sensation and motor function can significantly improve, and pain symptoms are markedly reduced, this case demonstrates that small needle-knife treatment can serve as a safe and effective minimally invasive therapeutic method.